High myopia and glaucoma susceptibility : The Beijing eye study - LIANG XU; YAXING WANG; SHUANG WANG; YUN WANG; JONAS, Jost B (Ophthalmology (Rochester, Minn.), 2007)
To evaluate whether marked myopia, compared with moderate myopia and low myopia, is associated with a higher prevalence of glaucomatous optic nerve damage. Population-based cross-sectional study. Four thousand four hundred thirty-nine of 5324 subjects 40 years or older were invited to participate (response rate, 83.4%). The group was stratified according to refractive error into high myopia (myopia > -8 diopters [D]), marked myopia (<-6 to -8 D), moderate myopia (<-3 to -6 D), low myopia (<-0.5 to -3 D), emmetropia (-0.5 to + <2 D), and hyperopia (>+ 2 D) subgroups. Morphologic assessment of optic disc monoscopic photographs. Morphologic optic disc parameters and intraocular pressure (IOP). For 4319 (97.3%) subjects (8484 eyes), optic disc photographs were evaluated. Prevalence of glaucomatous optic nerve atrophy as defined by the glaucomatous optic nerve head appearance did not vary significantly (P = 0.77; odds ratio [OR], 1.2; 95% confidence interval [CI], 0.38-3.81) between the highly myopic group and the group with marked myopia. In both refractive groups combined, glaucoma frequency seemed to be higher (P = 0.075; OR, 2.28; 95% CI, 0.99-5.25) higher than in the group with moderate myopia; it was significantly (P = 0.001; OR, 3.5; 95% CI, 1.71-7.25) higher than in the group with low myopia; significantly (P<0.001; OR, 7.56; 95% CI, 3.98-14.35) higher than in the group with emmetropia; and significantly (P = 0.005; OR, 4.23; 95% CI, 1.57-11.45) higher than in the group with hyperopia. Glaucoma frequency did not vary significantly between the hyperopic group and the emmetropic group (P = 0.17), the group with low myopia (P = 0.83), and the group with moderate myopia (P = 0.32). Intraocular pressure did not vary significantly (P>0.10) between any of the subgroups. Similar results were obtained for the frequency of glaucoma defined as glaucomatous optic disc appearance and visual field defects. In binary logistic regression analysis, presence of glaucoma was significantly associated with the myopic refractive error (P<0.001), age (P<0.001), and IOP (P<0.001). Marked to high myopia with a myopic refractive error exceeding -6 D may be a risk factor associated with glaucomatous optic neuropathy.